2011
DOI: 10.1017/s0025315410002079
|View full text |Cite
|
Sign up to set email alerts
|

New species of excavating sponges (Porifera: Demospongiae) on coral reefs from the Mexican Pacific Ocean

Abstract: Three new species of coral reef boring sponges were found in remote coral reefs from Revillagigedo Island, an archipelago that is 386 km from the continent.Cliona medinaesp. nov. is a sponge with orange-yellow papillae characterized by short almost straight spirasters.Cliona tropicalissp. nov., is a yellow papillate sponge with a spicule complement similar to the species included in theCliona viridiscomplex. However, the new species differs from the rest of the species mainly in its external morphology and by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 31 publications
0
18
0
1
Order By: Relevance
“…Accordingly, isolation by distance is a potential mechanism of differentiation and both low dispersal potential and physical factors, such as hydrological conditions, may play a significant role in shaping the genetic structure of sponges (Duran et al 2004c). In the Mexican Pacific (MP), studies concerned with coral-excavating sponges have focused primarily on their taxonomic description and classification, reproductive biology, and ecological role in reef communities (Carballo et al 2004;Carballo and CruzBarraza 2005;Bautista-Guerrero et al 2006;Carballo et al 2007;Nava and Carballo 2008;Bautista-Guerrero et al 2010;Cruz-Barraza et al 2011;Carballo et al 2013b;Bautista-Guerrero et al 2014). At present, the population genetic structure of coral-excavating sponges in this region remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, isolation by distance is a potential mechanism of differentiation and both low dispersal potential and physical factors, such as hydrological conditions, may play a significant role in shaping the genetic structure of sponges (Duran et al 2004c). In the Mexican Pacific (MP), studies concerned with coral-excavating sponges have focused primarily on their taxonomic description and classification, reproductive biology, and ecological role in reef communities (Carballo et al 2004;Carballo and CruzBarraza 2005;Bautista-Guerrero et al 2006;Carballo et al 2007;Nava and Carballo 2008;Bautista-Guerrero et al 2010;Cruz-Barraza et al 2011;Carballo et al 2013b;Bautista-Guerrero et al 2014). At present, the population genetic structure of coral-excavating sponges in this region remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the last two decades, knowledge has increased significantly and has shown that there is a higher diversity of sponges than previously thought (Desqueyroux‐Faúndez & van Soest, ; Lehnert, Stone & Heimler, ; Carballo et al ., , ; Cruz‐Barraza et al ., , ), which suggests a potentially high unexplored diversity of cryptic sponges in the eastern Pacific.…”
Section: Discussionmentioning
confidence: 98%
“…Three species described here are new to science, two Plakina and one Plakortis . This is also one of the few studies that includes Porifera records from the Revillagigedo and Clipperton Islands (Cruz‐Barraza et al ., , ; van Soest et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…; Cruz‐Barraza et al. ), which suggests that they could play an important ecological function on these coral reefs, and this also highlights the need to know their role in the current decline of these ecosystems. Given that coral‐bleaching events have become more frequent and intense in response to recent climate‐change‐related temperature anomalies, and it will probably become even more intense and severe, as temperatures are projected to continue to rise under the scenarios for future climate change (IPCC ), we think that it is important to know the status of boring sponge assemblages in coral reefs, especially in coral reefs strongly impacted by past bleaching and El Niño events.…”
Section: Introductionmentioning
confidence: 99%
“…In the Eastern Pacific coast, 46% of the total distribution of coral reefs spreads out along the Mexican Pacific coast, and some of the most severely damaged coral reefs by El Niño events are in this region (Carriquiry et al 2001;L opez-Perez and Hern andez-Ballesteros 2004). It is well-known that boring sponges from the Mexican Pacific coast invade different calcareous substrata (Carballo et al 2004(Carballo et al , 2007Bautista-Guerrero et al 2006;Cruz-Barraza et al 2011), which suggests that they could play an important ecological function on these coral reefs, and this also highlights the need to know their role in the current decline of these ecosystems. Given that coral-bleaching events have become more frequent and intense in response to recent climate-change-related temperature anomalies, and it will probably become even more intense and severe, as temperatures are projected to continue to rise under the scenarios for future climate change (IPCC 2007), we think that it is important to know the status of boring sponge assemblages in coral reefs, especially in coral reefs strongly impacted by past bleaching and El Niño events.…”
Section: Introductionmentioning
confidence: 99%